Embedded trilayer graphene flakes under tensile and compressive loading. (12th May 2015) - Tsoukleri, G; Parthenios, J; Galiotis, C; Papagelis, K
Abstract: The mechanical response of embedded ABA trilayer graphene flakes loaded in tension and compression on polymer beams is monitored by simultaneous Raman measurements through the strain sensitivity of the G or 2D peaks. A characteristic peculiarity of the investigated flake is that it contains a trilayer and bilayer part. The Bernal stacked bilayer was used as a strain sensor aiming to assess the efficiency of the load transfer from the polymer matrix through shear to the individual graphene layers. For the trilayer graphene in tension, both peaks are redshifted and splitting of the G peak is reported for the first time. In compression, the studied sample was an almost isolated trilayer, in which both peaks are blue-shifted up to a critical compressive strain. This critical strain is found to be one fourth of the value found in the case of single layer graphene despite the higher bending rigidity that trilayer exhibits over the much thinner monolayer.